Zest : a driving force in motors - Gaylard, Alison; Bick, Geoff ([London] : SAGE, 2016)
Johannesburg-based Zest, well respected in the electric motor industry, was the only distributor of WEG motors throughout southern Africa. In 2001, its chief executive officer (CEO), James Blakemore, added variable speed drives (VSDs) to the product portfolio and, by 2009, Zest had become the fourth-biggest player in the local drives market. Now, in July 2009, Blakemore pondered his options. Should he focus on increasing market share and boosting sales? Or had the time come to diversify once more?
Originally Published in: Gaylard, A., & Bick, G. (2010). Zest: A Driving Force in Motors. WBS-2010-01. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Zest (Firm); Industrial marketing -- Case studies; Marketing -- Management -- Case studies